Breaking the BIT Mold: Brazil's Pioneering Approach to Investment Agreements. (27th August 2018) - Choer Moraes, Henrique; Hees, Felipe
Abstract : Brazil only recently joined the collection of states that have adopted international investment agreements (IIAs), but in doing so it developed a noteworthy approach in the form of the Cooperation and Facilitation Investment Agreement (CFIA). In this essay, we explore the characteristics and merits of this particular treaty model, making three points: First, the CFIA exhibits unique features that set it apart from traditional bilateral investment treaties (BITs), including the state-to-state management of investment relations and an emphasis on investment facilitation rather than investment protection . Second, the CFIA displays a degree of "interoperability" that has made it possible for Brazilian partners to sign these agreements while simultaneously holding BIT portfolios, despite significant differences between the two approaches. Finally, one of the CFIA's key features—that of investment facilitation—is a promising basis for reform in multilateral settings such as the World Trade Organization (WTO). In short, we believe that the CFIA offers an innovative and attractive option for states looking to supplement or revise traditional BITs, both bilaterally and multilaterally.